Efisiensi Teknis Pendidikan Menengah pada Daerah Pemekaran di Kawasan Timur Indonesia - Fitri Amalia; Nadiya Mawaddah (Universitas Indraprasta PGRI Jakarta, 2023)
Education is human capital for the future. Secondary education is the focus for continuing education or a career. The newly created regions are expected to provide public services more efficiently, especially in terms of primary and secondary education services. This study aims to determine the technical efficiency of secondary education in the expansion areas in eastern Indonesia. The period in this study was in 2018-2021. The method used in this research was Data Envelopment Analysis (DEA) with output orientation and the Variable Return to Scale (VRS) model. The focus of the Decision-Making Units (DMU) in this research was the provinces experiencing division in eastern Indonesia, namely the provinces of North Maluku, West Sulawesi, Gorontalo and West Papua. The inputs used were the number of schools, the number of teachers, the number of students, class conditions, and the Indonesian smart card budget. Meanwhile, the output used was the average length of schooling, school enrolment rates, and continuing rates. The results of this study indicate that the province of North Maluku in the 2018, 2019 and 2021 periods experienced inefficiency, while in 2020 it experienced efficiency. In contrast to West Sulawesi, Gorontalo and West Papua during the period experienced efficiency.